2017
DOI: 10.1039/c6md00593d
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, molecular-docking and antimycobacterial evaluation of some novel 1,2,3-triazolyl xanthenones

Abstract: As part of an ongoing effort to develop new antitubercular and antimicrobial agents, a series of substituted xanthenone derivatives () were synthesized. Xanthenone derivatives () were prepared a one-pot three-component thermal cyclization reaction of β-naphthol (), substituted 1-aryl-1-[1,2,3]triazole-4-carbaldehydes (), and cyclic-1,3-diones (, ) in the presence of a catalytic amount of iodine. The newly synthesized compounds were characterized by IR, NMR, mass spectral data, and elemental analysis. These com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Therefore, special concern should be devoted to the development of new antimicrobial agents, possessing completely different chemical structures, and working with different modes of actions. The Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC) reaction offers a versatile synthetic access to the 1,2,3-triazole heterocycle derivatives, which are associated with a wide spectrum of pharmacological activities, including antimycobacterial [18][19][20][21], antitubercular [22][23][24][25], anticancer [26][27][28][29], antiviral [30][31][32][33][34], antidiabetic [35][36][37][38], antifungal [39][40][41][42], anti-HIV [43][44][45][46], anti-inflammatory [47][48][49][50], antimalarial [51][52][53][54], anti-oxidant [55][56][57][58], anti-proliferative [59][60][61][62] properties. The 1...…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, special concern should be devoted to the development of new antimicrobial agents, possessing completely different chemical structures, and working with different modes of actions. The Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC) reaction offers a versatile synthetic access to the 1,2,3-triazole heterocycle derivatives, which are associated with a wide spectrum of pharmacological activities, including antimycobacterial [18][19][20][21], antitubercular [22][23][24][25], anticancer [26][27][28][29], antiviral [30][31][32][33][34], antidiabetic [35][36][37][38], antifungal [39][40][41][42], anti-HIV [43][44][45][46], anti-inflammatory [47][48][49][50], antimalarial [51][52][53][54], anti-oxidant [55][56][57][58], anti-proliferative [59][60][61][62] properties. The 1...…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with excellent in vitro potency in the MTB MIC were further tested for toxicity. As a result, Compounds 41a and 41b showed 18.10% inhibition and 18.12% inhibition at 50 μg/ml in an HEK cell line, respectively (Goud et al, )).…”
Section: Five‐membered Ring Compoundsmentioning
confidence: 99%
“…Moreover, derived of the 1,3-cyclohexadione type 10a containing methyl groups (i.e., R = Me) did not display activity. The molecular docking studies of compounds active against pantothenate synthetase revealed the favorable interactions with amino acid residues of such enzyme [89].…”
Section: Anti-mycobacterial Activitymentioning
confidence: 99%